Prognostic value of fluorodeoxyglucose positron emission tomography/computed tomography and inguinal sentinel lymph node biopsy in patients with anal cancer. (5th June 2019) - De Nardi, P.; Guarneri, G.; Canevari, C.; Tamburini, A.; Slim, N.; Passoni, P.; Rosati, R.
Abstract: Aim: The aim of this study was to assess the value of positron emission tomography (PET)/CT and sentinel lymph node (SLN) biopsy in staging inguinal lymph nodes in anal cancer patients and to determine if the results of the two methods could be of prognostic value. Method: Sixty‐three patients with anal cancer and clinically negative inguinal lymph nodes underwent lymphoscintigraphy and inguinal SLN biopsy and/or fluorodeoxyglucose (FDG) PET/CT scan. All patients were treated with radiotherapy combined with 5‐fluorouracil and mitomycin‐C. Results: Overall (OS) and disease‐free survival (DFS) were 43 months (range 5–211) and 43 months (range 4–142) respectively. PET/CT examination showed high FDG uptake in the inguinal lymph nodes in 25% of patients. Thirty‐five patients with inguinal uptake at lymphoscintigraphy underwent inguinal SLN biopsy and metastatic nodes were found in 31.4%. There was no statistical difference in OS (55 vs 41 months; P = 0.652) and DFS (48 vs 38 months; P = 0.992) between the group which showed inguinal uptake on PET/CT and the group which did not, while a positive inguinal SLN was associated with a worse OS (28 vs 59 months; P = 0.028) and DFS (56 vs 21 months; P = 0.046). When the two examinations were compared PET/CT showed a sensitivity, specificity, positive predictive value and negative predictive value of 22%, 82%, 33% and 73% respectively. Conclusion: The technique of SLN biopsy had a better diagnostic accuracy than total body FDG‐PET/CT for the staging of inguinal lymph nodes in anal cancer patients; moreover it was a stronger predictor of OS and DFS than PET/CT.